1981
DOI: 10.1073/pnas.78.10.6548
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal action potentials associated with the Shaker complex locus of Drosophila

Abstract: Intracellular recordings ofaction potentials were made from the cervical giant axon in Shaker (Sh) mutants and normal Drosophila. The mutants showed abnormally long delays in repolarization. The defect is not due to abnormal Ca2+ channels, because it persists in the presence of Co2+, blocker. On the other hand, the K+-channel blocker 4-aminopyridine causes a similar effect in normal animals, suggesting that the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(83 citation statements)
references
References 17 publications
6
77
0
Order By: Relevance
“…This is consistent with the electrophysiological phenotype of Sh mutants that produces modifications in neurotransmitter release (Jan et al, 1977) and action potentials (Tanouye et al, 1981). The most intense expression of Sh Kch found in defined regions of the adult head such as MB and OL neuropile agrees with that found in an earlier immunohistological study (Schwarz et al, 1990).…”
Section: Diverse Functional Roles Can Be Inferred From the Distributisupporting
confidence: 89%
“…This is consistent with the electrophysiological phenotype of Sh mutants that produces modifications in neurotransmitter release (Jan et al, 1977) and action potentials (Tanouye et al, 1981). The most intense expression of Sh Kch found in defined regions of the adult head such as MB and OL neuropile agrees with that found in an earlier immunohistological study (Schwarz et al, 1990).…”
Section: Diverse Functional Roles Can Be Inferred From the Distributisupporting
confidence: 89%
“…At the larval neuromuscular junction, the Sh mutations have been associated with antidromic repetitive firing of motor axons resulting in prolonged transmitter release (Jan et al, 1977;Wu, 1982b, 1983). Intracellular recordings from adult giant axons revealed abnormal action potentials with delayed repolarization (Tanouye et al, 1981). Recent voltage clamp studies of adult (Salkoff and Wyman, 1981;Salkoff, 1983b) and larval muscles (Wu et al, 1983a;Wu and Ganetzky, 1984) confirm the previous suggestion that Sh mutations affect potassium currents (Jan et al, 1977).…”
supporting
confidence: 60%
“…The defects caused by Sh5 have been found to be consistently less extreme than those in ShKS'33 In all tissues examined (larval neuromuscular junctions: Jan et al, 1977; C. -F. Wu and B. Ganetzky, unpublished observations; adult "giant axons": Tanouye et al, 1981;adult muscles: Salkoff and Wyman, 1981; larval muscles: this report). However, voltage clamp studies of the residual IA in Sh5 revealed important differences in the manner in which adult and larval muscles are affected.…”
Section: The Journal Of Neuroscience Potassium Currents In Drosophilamentioning
confidence: 68%
See 1 more Smart Citation
“…Little is known, however, about how the electrical activities of central neurons are affected. Intracellular recording of action potentials has been performed on certain Drosophila neurons in vivo (Ikeda and Kaplan, 1974;Tanouye et al, 1981), but additional electrophysiological analyses have been limited by technical difficulties. The Drosophila "giant" neuron culture system has provided a preparation accessible to electrophysiological characterizations of neuronal activity and the underlying ionic currents Wu, 1991, 1993;Zhao and Wu, 1994).…”
mentioning
confidence: 99%